STUDI PENGARUH JARI-JARI DALAM MAGNET TERHADAP TEGANGAN GENERATOR AKSIAL PADA BAHAN CAKRAM AKRILIK - Pebri Prihatmoko; F. Danang Wijaya; Suharyanto Suharyanto (Universitas Gadjah Mada, 2019)
The high cost of making rotor discs is one aspect that becomes an obstacle in the implementation of axial generator research. This study aims to compare acrylic discs with wooden discs in terms of axial generator output voltage and production costs, so that further research can use alternative discs with lower cost. This study uses an experimental method, where this method is used to find existing variables. On a generator with an acrylic disc, the average voltage is 16.6 volts with a manufacturing cost of 151,500 rupiah. Whereas on generator with wood disc, the average voltage is 17.2 volts with a manufacturing cost of 48,750 rupiah. Thus wood disc can be an alternative material in making cheap axial generator rotor discs.